Behavioral and Neuroanatomical Consequences of Cell-Type Specific Loss of Dopamine D2 Receptors in the Mouse Cerebral Cortex - Lee, Gloria S.; Graham, Devon L.; Noble, Brenda L.; Trammell, Taylor S.; McCarthy, Deirdre M.; Anderson, Lisa R.; Rubinstein, Marcelo; Bhide, Pradeep G.; Stanwood, Gregg D. (Frontiers in Behavioral Neuroscience, 2022)
Developmental dysregulation of dopamine D2 receptors (D2Rs) alters neuronal migration, differentiation, and behavior and contributes to the psychopathology of neurological and psychiatric disorders. The current study is aimed at identifying how cell-specific loss of D2Rs in the cerebral cortex may impact neurobehavioral and cellular development, in order to better understand the roles of this receptor in cortical circuit formation and brain disorders. We deleted D2R from developing cortical GABAergic interneurons (Nkx2.1-Cre) or from developing telencephalic glutamatergic neurons (Emx1-Cre). Conditional knockouts (cKO) from both lines, Drd2fl/fl, Nkx2.1-Cre+ (referred to as GABA-D2R-cKO mice) or Drd2fl/fl, Emx1-Cre+ (referred to as Glu-D2R-cKO mice), exhibited no differences in simple tests of anxiety-related or depression-related behaviors, or spatial or nonspatial working memory. Both GABA-D2R-cKO and Glu-D2R-cKO mice also had normal basal locomotor activity, but GABA-D2R-cKO mice expressed blunted locomotor responses to the psychotomimetic drug MK-801. GABA-D2R-cKO mice exhibited improved motor coordination on a rotarod whereas Glu-D2R-cKO mice were normal. GABA-D2R-cKO mice also exhibited spatial learning deficits without changes in reversal learning on a Barnes maze. At the cellular level, we observed an increase in PV+ cells in the frontal cortex of GABA-D2R-cKO mice and no noticeable changes in Glu-D2R-cKO mice. These data point toward unique and distinct roles for D2Rs within excitatory and inhibitory neurons in the regulation of behavior and interneuron development, and suggest that location-biased D2R pharmacology may be clinically advantageous to achieve higher efficacy and help avoid unwanted effects.